Analisis Penerapan PSAK 109 Pada Badan Amil Zakat Nasional Kota Tual - Ohoirenan, Moh Husain; Fithria, Annisa (AKTSAR: Jurnal Akuntansi Syariah, 2020)
This study aims to analyze the procedures of preparing financial statements at BAZNAS Kota Tual and the implementation of PSAK 109 on the financial statements of BAZNAS Kota Tual. This study uses a qualitative method by collecting the data through financial reports, literature, interview, and documentation. The results show that the financial reporting of zakat, infaq/sadaqah at BAZNAS Kota Tual has not fully implemented PSAK 109. Based on PSAK 109, the financial reporting of zakat, infaq/sadaqah uses five elements, i.e. initial recognition, measurement, distribution, presentation, and disclosure. However, practically, BAZNAS Kota Tual only implements a few elements, namely initial recognition and distribution. BAZNAS Kota Tual has not implemented measurement, presentation, and disclosure. Moreover, BAZNAS Kota Tual does not make complete financial reports, such as the balance sheets, reports on changes in funds, reports on changes in assets under management, cash flow reports, and notes on financial reports, but only make a simple report, namely the report on the collection and distribution of zakat, infaq/sadaqah.